Pengaruh Penilaian Kinerja Terhadap Promosi Jabatan Di PT. X Semarang - Sari, Amanda Puspita; Rahayu, Puspita Puji (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2024)
This article aims to determine the effect of performance appraisal on job promotions for employees at PT. X Semarang. The problem focuses on the performance assessment used by PT. X Semarang. To approach this problem, theoretical references from Mathis and Jackson are used. Data was collected through a research scale distributed via Google Form and analyzed using statistical analysis, namely simple linear regression analysis which was used to find out how big the influence of performance appraisal was. The researcher chose simple linear regression analysis as a research methodology to test how big the causal relationship is between the independent variable (X) and the dependent variable (Y). The questionnaire distribution strategy was carried out via Google Form by sharing the Google Form link with several PT employees. X Semarang. This study concludes that performance appraisal has a positive effect on promotion with a total effect of 22.7%. This positive influence means that the higher the performance assessment results, the greater the opportunities for employees at PT. X Semarang received a promotion. Meanwhile, the other 77.3% of job promotions were influenced by other factors, including higher level educational background (starting work only as a high school graduate and during work taking undergraduate education until graduation), work experience held as well as certificates and other skills. which are owned.